PERSONALITY PROBLEM IN SOCIAL PSYCHOLOGY - Toshpulatov Ibrohim Ikromjonovich; Abduxapizov Samandarbek Abdulkosim o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
this article examines the problem of personality, the uniqueness of learning for social psychology, types of personality and their social psychological characteristics, personality and group problems.